Adab Siswa Mengikuti Program Tahfidzul Qur’an Di MTsN 5 Agam - Wenita Saputri; Charles Charles; Afrinaldi Afrinaldi; Muhiddinur Kamal (BADAN PENERBIT STIEPARI PRESS, 2023)
The background of this research is that some students who memorize the Qur'an are people who have good manners, because adab can affect the character and attitude of students whose learning of the Koran already reflects people who are very meaningful with regard to aspects of behavior. a person both personally and in relation to his social aspects. This type of research is a descriptive qualitative research that describes the adab of students participating in the Tahfidzhul Qur'an Program at MTsN 5 Agam. In collecting data researchers used observation techniques, interviews and documentation. Meanwhile, to analyze it, the researcher uses data reduction, data presentation and conclusion drawing. Based on the research results to data processing, it was found that the etiquette of students who took part in the Tahfidzhul Qur'an activity program already reflected students who had good manners. Students always remember Allah SWT and never forget it, always obey and never do things that are prohibited by Allah SWT, and also always pay attention to Allah. Students always reflect someone who has good manners. It can also be seen that students always make their intentions sincere only because of Allah SWT., and also have an attitude that reflects someone who memorizes the Qur'an who is always polite, polite and respectful to his teacher.